Deslocamento de caráter em hilídeos neotropicais (anura: hylidae) - Cholak, Luiza Rieder [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The interspecific competition tends to favor the selection of divergent phenotypes minimizing the effect of this interaction. This process is termed character displacement and it is considered one of the main mechanisms promoting adaptive diversification. Brazil has the greatest diversity of amphibians on the planet and despite this great diversity; the role of character displacement in the process of Brazilian amphibian fauna diversification has not been studied. In the present study we tested the hypothesis of character displacement in four congeneric species pairs of frogs from the family Hylidae, occurring in the Atlantic Forest and Cerrado. We find evidence of character displacement for two pairs and parallel evolution for the remaining. Interestingly, the trend of character displacement was in species whose range covers less stable habitats. Since this is a pioneering study with neotropical hylid, we discussed issues considered relevant to elucidate mechanisms related to the maintenance of diversity

A competição interespecífica tende a favorecer a seleção de fenótipos divergentes minimizando o efeito desta interação. Este processo é denominado deslocamento de caráter e é considerado um dos principais mecanismos promotores da diversificação adaptativa. O Brasil apresenta a maior diversidade de anfíbios do planeta e apesar desta grande diversidade, o papel do deslocamento de caráter no processo de diversificação da fauna de anfíbios brasileiros ainda não foi estudado. No presente estudo testamos a hipótese de deslocamento de caráter em quatro pares de espécies congenéricas de anfíbios anuros da família Hylidae, que ocorrem na Mata Atlântica e no Cerrado. Encontramos evidência de deslocamento de caráter para dois dos pares de espécie e evolução paralela para os demais. Interessantemente, a tendência de deslocamento de caráter existiu em espécies cuja distribuição abrange habitats menos estáveis. Por se tratar de um estudo pioneiro com hilídeos neotropicais, abordamos questões consideradas relevantes para elucidar mecanismos relacionados à manutenção da diversidade
Keywords: Anuro; Competição (Biologia); Corpo - Tamanho; Fisiologia comparada; Biodiversidade; Morfologia (Animais); Evolução (Biologia); Adaptação (Biologia)